The Implementation of the Storytelling Method Using Digital Media to Increase Reading Interest - Nayla Salsa Billa; Suci Perwita Sari (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to improve the reading interest of students at Sanggar Belajar Pandan, Kuala Lumpur, Malaysia, through the implementation of the storytelling method using digital media. The research was conducted using a Classroom Action Research (CAR) method with 20 student participants. The results showed a significant increase in students' reading interest after the application of digital-based storytelling. In the pre-action phase, most students were in the low or poor reading interest category, with a percentage of 47%. However, after the first session of digital storytelling in Cycle I, there was an increase, with the average percentage rising to 62.1%. Further improvement was recorded during the second session of Cycle I, where all students' reading interest reached the “very good” category, with an average percentage of 87.4%. Moreover, students’ responses to the effectiveness of the digital storytelling method showed that it was highly effective in increasing reading interest, with 82.1% of students rating it as “very effective.” Thus, it can be concluded that the implementation of the storytelling method using digital media is highly effective in enhancing the reading interest of students at Sanggar Belajar Pandan, Kuala Lumpur, Malaysia.